Perfluorooxasulphonates of metals – the catalysts of esters manufacture - Melnyk, Stepan (Publishing House of Lviv Polytechnic National University, 2013)
The process of obtaining of aliphatic dibasic esters from dicarboxylic acids and C4-C5 alcohols in the presence of perfluoro(4–methyl–3,6–dioxaoctane)sulphonates of different metals has been researched. For the comparative estimation of catalysts their concentration was chosen identical and of such value that the rate of the process was limited exactly by the rate of chemical reaction. The dependences of technological characteristics of esterification process on catalyst nature and concentration and on reagents nature have been determined. High activity of the investigated catalysts has been found out, which is probably caused by the synergetic effect of metal cation and perfluoroic fragment,which provides decreasing of electron density on metal ion and at the same time good solubility of catalyst in the substrate, thus providing its high active concentration. Досліджено процес одержання естерів аліфатичних дикарбонових кислот і спиртів С4-С5 у присутності перфтор(4-метил-,6-діоксаоктан)сульфонатів різних металів. Для порівняльної оцінки каталізаторів їх концентрація вибрана однаковою і такою, щоб швидкість процесу лімітувалася саме швидкістю хімічної реакції. Отримано залежності впливу концентрації та природи каталізатора, природи дикарбонової кислоти та спирту на технологічні показники процесу естерифікації. Виявлена досить висока активність досліджених каталізаторів, яка, ймовірно, обумовлена синергічним ефектом дії катіону металу і перфторованого фрагмента, який забезпечує як зменшення електронної густини на йоні металу, так і добру розчинність каталізатора в субстраті і створення його високої активної концентрації.
Перфтороксасульфонати металів - каталізатори одержання естерів
Keywords: esterification; dicarboxylic acids; perfluorooxasulphonates; catalysts; C4-C5 alcohols; естерифікація; дикарбонові кислоти; перфтороксасульфонати; каталізатор; спирти С4-С5